Heterosis and breed percentage effects on reproductive performance and preweaning traits in a multibreed beef cattle herd in Panama - Gonzalez Murray, Roderick Alexander, author; Speidel, Scott E., advisor; Enns, R. Mark, advisor; Thomas, Milton G., committee member; Coleman, Stephen J., committee member; Holt, Timothy, committee member (Colorado State University. Libraries, 2023)
Panama is located in Central America and is characterized by a tropical climate. Given the tropical climate conditions, Zebu cattle (Bos indicus) are the most predominant breeds in cow–calf systems due to greater resistance to internal and external parasites, and greater tolerance to elevated ambient temperatures and humidity when compared to Bos taurus beef breeds. Zebu is a breed that is reproductively inefficient due to Age at First Calving (AFC) being over 36 months and having longer calving intervals (CI), ranging between 12.2 to 26.6 months. The Panamanian cow-calf system reports an average annual birth rate of 55%, with a range of 35% to 60%, depending on the province. This reduced efficiency reported in the cattle production system is also reflected in low kilograms of weaned calves per cow exposed to AI or Bull (80kg) to 120 WW/cow exposed), high age at first calving (over 36 months), long calving interval (more than 450 days), and perhaps low-income returns ranging between 8 to 15% per dollar invested. The reproductive efficiency of a herd is one of the main components of a cow-calf system economically. Other important traits that affect the system efficiency and profitability are the preweaning traits: birth weight (BW) and weaning weight (WW). The lack of system efficiency and profitability is why different breeds have been introduced to the country to be used in crossbreeding systems to obtain the benefits of heterosis in growth and reproductive traits. The beneficial effects of crossbreeding on animal performance have been well established, benefiting low heritability traits such as those related to reproduction. For that reason, in tropical environments, matching the optimum cow numbers with the correct genetic potential in the appropriate production environment can maximize economic benefits. In the tropics, reduced pre- and post-weaning growth and reproductive efficiency are the main limiting factors in the cow-calf system. Preweaning traits are a combination of the direct genetic, maternal genetic, maternal permanent environment, and temporary environmental effects. The challenge for farmers in Latin American countries is to identify those animals that achieve maximum productive performance in a given agro-ecological environment, and to maintain a balance between longevity and generation intervals, in order to obtain the greatest genetic gain per unit of time. Knowledge of the genetic effects of breeds and their crosses in various climatic and forage conditions can be used to identify optimal breed combinations and crossbreeding systems for existing markets. Based on the heterogeneity of herds in tropical regions due to the introduction of multiple breeds and the different crossbreeding systems utilized, it is necessary to carry out a multibreed evaluation that includes all crossbred and purebred individuals into a single analysis and accounting for the direct and maternal breed and heterosis effect evaluation. As we mentioned above, different breeds have been introduced in Panamá, but no genetic evaluation program has been developed in the country, to improve the efficiency of cow-calf production. However, it is important to evaluate the breed groups and heterosis effect through productivity indicators to know the relative performance of the breeds and crosses of Zebu and Bos taurus cattle in the cow–calf system. Therefore, the objectives of this study were to determine heterosis and breed percentage effects on reproductive performance and preweaning traits in a multibreed beef cattle herd in Panama. For this, traits like age at first calving (AFC), calving interval (CI), gestation length (GL), birth weight (BW), and weaning weight (WW) that constitute important elements of the breeding objective of beef cattle producers were selected as the traits to evaluate in this study. All the reproductive and preweaning data utilized in this investigation was produced by a multibreed cattle population of the Livestock Experimental Station of Panama Agricultural Innovation Institute (IDIAP) in Gualaca, province of Chiriqui, Republic of Panama. The herd was comprised of the following genetic groups and breed percentage combinations: tropical adapted Brahman (BR), Nellore (Ne), Undefine Bos indicus (BI), Guaymi Creole (CR), Senepol (SP) Romosinuano (RS); Bos taurus (BT), Simmental (SM), Angus (AN), Red Angus (AR), Limousin (LM), Charolais (CH), Wagyu (WA), and Others (OTH); crossbreeds (CX), Beefmaster (BF), Three CX (F1 x different BT), R1(Backcross BR), R2 (Backcross BT), Composite (combination of at least 4 different breeds with less than 25% of Zebu), Upgraded Brahman (87.5% BR 12.5% BT), B1 (62.5% Zebu + 37.5% BT), B2 (62.5% BT + 37.5% Zebu). In general, this dissertation was divided into three different studies according to the physiological status of the individual producing the phenotypic record (e.g., calf, heifer, and multiparous cows). The first study estimated the influence of heterosis and breed percentage on age at first calving (AFC). An animal model was utilized to estimate variance components using data from 619 cows and 1,142 individuals in the pedigree from the multibreed herd with data collected between 2000 to 2019. The average AFC was 42.7 ± 10.5 months, with an estimated regression coefficient for AFC on heterosis of -0.046 ± 0.009 month/percent of outcross. Lower AFC was observed for the F1, R2, and B2, with 39.8 months, 39.9 months, and 39.5 months, respectively. A reduction in AFC was also observed for the Beefmaster (-0.13 ± 0.05 months) and the OTHER category (-0.14 ± 0.04 months). A heritability of 0.17  0.10 was estimated for AFC. These results suggest that heterosis had a beneficial influence on AFC measurements in a multibreed beef cattle herd in Panama. The second study focused on estimating the influence of heterosis and breed percentage on calving interval (CI) and gestation length (GL), and the correlation between age at first calving (AFC) and CI. Calving performance data included 1,291 repeated observations of CI and GL from 502 cows with a 3-generation pedigree consisting of 2,840 individuals in the pedigree with data collected between 2000 to 2021. A repeated records animal model was utilized to estimate variance components for both CI and GL. Additionally, a bivariate animal model was used to estimate the genetic correlation between CI and AFC. The average CI was 572.6 ± 140 days, and for GL was 284.2 ± 6.3 days, for this population. The regression of CI and GL on heterosis was not significant. A lower CI was observed for the F1, and Three CX, translating to 558.7 days and 567.2 days, which represents 2.3% and 1.3% reduction in CI, respectively when compared to the Zebu group. Calving interval was estimated to be lowly heritable (0.037 ± 0.026), however, a positive genetic trend over the duration of the study. The analysis between CI and AFC revealed a moderate genetic correlation (0.49 ± 0.36) which allows the establishment of a selection program to improve AFC and CI, due to the pleiotropic effect, which would improve the fertility of this multibreed herd in Panama. Finally, the third study aimed to estimate the influence of heterosis and breed percentage on birth weight (BW) and weaning weight (WW). Data from 900 calves with 2,843 individuals in the pedigree was utilized in a bivariate animal model for BW and WW was utilized to estimate variance components. The estimated regression coefficient for BW on heterosis was not significant, however, for WW was 0.072 ± 0.027 kg/percent of outcross. Lower BW and WW were observed for the Japanese, and B1, while R2 and Upgrade had the highest average WW. Heritability for BW was found to be low 0.14 ± 0.06 and moderate for WW 0.26 ± 0.09. The proportion of variation of WW accounted by the maternal permanent environment for WW was 0.2 ± 0.09. The estimated genetic correlation between additive genetic BW and WW was 0.63 ± 0.30, while a negative, additive genetic correlation was observed for WW and WW maternal -0.43 ± 0.37. These results suggested that heterosis had a beneficial influence on WW but a limited effect on BW. Additionally, increasing the percentage of WA and BR negatively influenced WW measurements in this multibreed population.
Keywords: claving interval; multibreed; reproduction; heterosis; age at first calving; preweaning